VeRSiert - Sicherheit im ÖPNV bei Großveranstaltungen. Vernetzung von Verkehrsunternehmen, Einsatzkräften, Veranstaltern und Fahrgästen des ÖPNV. - (:unkn) unknown (Buchwerft-Verl., 2011)
Das Projektkonsortium VeRSiert hat im Auftrag des BMBF im Untersuchungsraum Köln technische und organisatorische Mittel entwickelt, mit denen die Verantwortlichen bei einer erfolgreichen Planung und einer sicheren Durchführung von Großveranstaltungen unterstützt werden können. Das Buch zeigt die Ergebnisse der dreijährigen Forschungstätigkeit auf und veranschaulicht den Nutzen für kommende Veranstaltungen.

Big events are growing in numbers and importance for communities and require a high level of conceptual and operational framework for those involved. In doing so, the variety of involved organization and actors need to be coordinated effectively. In order to increase the safety for the arrival and departure of the visitors, innovative approaches with a well-linked traffic management are required. Within the research project VeRSiert (versed) supported by the Federal Ministry of Education and Research, scientists and specialists have developed new solutions for an optimum and cross-organizational communication. Components of this integrated system are video analysis, simulation and a web supported information and cooperation port.
Big events - a challenge for the local passenger transport.
Keywords: Verkehr; ÖPNV; Veranstaltungsstätte; Verkehrsanbindung; Fahrgastaufkommen; Verkehrsdichte; Verkehrsablauf; Verkehrssicherheit; Verkehrsregelung; Verkehrsplanung; Planungsgrundlage; Simulation; Information; Kommunikation; Kooperation; Überwachung; Forschungsprojekt; Großveranstaltung; Videoüberwachung; Fallbeispiel